2016
DOI: 10.3847/2041-8205/820/2/l23
|View full text |Cite
|
Sign up to set email alerts
|

THE MOSDEF SURVEY: THE STRONG AGREEMENT BETWEEN Hα AND UV-TO-FIR STAR FORMATION RATES FOR z ∼ 2 STAR-FORMING GALAXIES*

Abstract: We present the first direct comparison between Balmer line and panchromatic SED-based SFRs for z ∼ 2 galaxies. For this comparison we used 17 star-forming galaxies selected from the MOSFIRE Deep Evolution Field (MOSDEF) survey, with 3σ detections for Hα and at least two IR bands (Spitzer/MIPS 24 µm and Herschel/PACS 100 and 160 µm, and in some cases Herschel/SPIRE 250, 350, and 500 µm). The galaxies have total IR (8 − 1000 µm) luminosities of ∼ 10 11.4 − 10 12.4 L and star-formation rates (SFRs) of ∼ 30 − 250 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
73
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 44 publications
13
73
1
Order By: Relevance
“…In this case, the Hβ-to-FUV ratio is almost constant around −0.2 for all masses and seems to match the prediction of the IGIMF Minimal1 model (the purple dotted line in the left panel of Figure 5). However, as shown by other studies, the SFRs measured from FUV and nebular emission line are usually in very good agreement for massive galaxies (see W12 for z = 0 galaxies and Shivaei et al (2015Shivaei et al ( , 2016 for z ∼ 2 galaxies). Therefore, we suspect that the SMC curve "over-corrects" the dust extinction for massive galaxies to push their Hβ-to-FUV ratios to being significantly smaller than unity (i.e., negative in logarithmic scale).…”
Section: Effects Of Dust Extinction Correctionsupporting
confidence: 66%
“…In this case, the Hβ-to-FUV ratio is almost constant around −0.2 for all masses and seems to match the prediction of the IGIMF Minimal1 model (the purple dotted line in the left panel of Figure 5). However, as shown by other studies, the SFRs measured from FUV and nebular emission line are usually in very good agreement for massive galaxies (see W12 for z = 0 galaxies and Shivaei et al (2015Shivaei et al ( , 2016 for z ∼ 2 galaxies). Therefore, we suspect that the SMC curve "over-corrects" the dust extinction for massive galaxies to push their Hβ-to-FUV ratios to being significantly smaller than unity (i.e., negative in logarithmic scale).…”
Section: Effects Of Dust Extinction Correctionsupporting
confidence: 66%
“…Shivaei et al (2016) reported that for z ∼ 2 galaxies from the MOSFIRE Deep Evolution Field survey (MOSDEF, Kriek et al 2015), Hα-based estimates of SFR are consistent with those estimated from the full panchromatic SED (including UV and far-IR photometry). Dust extinction toward star-forming regions is estimated by comparing the Balmer decrement (Hα/Hβ) with the expected Case B value of 2.86 (Osterbrock 1989).…”
Section: Slit-loss Correctionsmentioning
confidence: 61%
“…Tanaka et al 2017, in preparation). While the SFRs might be overestimated for the less massive galaxies (e.g., see Figure 8 in Shivaei et al 2016), further investigation is beyond the scope of this paper. Since thegalaxies detected in Suzuki et al 2017, in preparation).…”
Section: Moircs/subaru Nir Data: Mstar and Sfrmentioning
confidence: 91%